Has criminalisation of the master subverted the aim of International Pollution Instruments to impose uniformity on the consequences of ship-source pollution? - Kapp, Catharina Wilna (Department of Commercial Law, 2022)
Ship's Masters frequently face criminalisation after a maritime accident. Even though international pollution instruments are unambiguous regarding the consequences of shipsource pollution, states often penalise the Master in a manner that is not consistent with their treaty obligations. It brings into question whether international pollution instruments' objective to impose uniformity in their application is subverted by states who impose sanctions on the Master, which defies the aim of the pollution instruments to which they are bound. The protection of the marine environment is strictly regulated in several international conventions to reduce the risk of pollution. The consequences of ship-source pollution are sufficiently clear-cut to ensure compliance by the shipping industry and provide states responsible for enforcing it with clarity. The reality is that states often impose harsh punitive measures on the Master when an accident leads to pollution, and he is often disproportionately criminalised despite the conventions' safeguards. During the last decade, the IMO and maritime industry partners have attempted to address criminalisation by appealing to states to treat seafarers fairly after a maritime accident. However, the facts indicate that states often circumvent the conventions to suit their prevailing circumstances. Although the criminalisation of the Master is an innately worrying factor for anyone who operates a ship or aspires to a career at sea, it is the persistent unwillingness of states to comply with their treaty obligations that poses the biggest threat to the industry. Why states may be motivated to circumvent the conventions are investigated and measured against the ramifications when states do not comply with their treaty obligations to establish whether states are deliberately subverting the aim of international pollution instruments to achieve uniformity. Indications are that the criminalization of the Master through defying the international pollution instruments has become the norm, and states are more driven by regional ethics than their treaty obligations. States tend to favour a punitive approach to pollution strongly and are highly likely to act in a manner inconsistent with their treaty obligations when ship-source pollution occurs in their waters.